Neuroprotective and Neurotrophic Effects of Lithium on Bipolar Disorder (2013)
ABSTRACT: Despite the development of other medications with mood-stabilising properties, such as atypical antipsychotics and antiepileptic drugs, lithium still remains the first-line treatment for bipolar disorder (BPD), and there is increasing evidence for the hypothesis of its neuroprotective and neurotrophic effects as key factors for its clinical effects. Methods: A literature research was conducted using the PubMed database without chronological or language limits to August 2012. The following MESH terms were used: Bipolar Disorder and Lithium combined with: Neuroprotective, Neurotrophic, Neurocognitive effects, GSK-3b, bcl-2, BDNF, hippocampal. Original studies and reviews were selected (in vitro, in vivo and clinical studies). Results: We found evidence in basic studies of neuroprotective and neurotrophic molecular pathways like GSK-3b, Bcl-2, BDNF, glutamate excitotoxicity, AP-1, mitochondrial dysfunction and neurosteroids. Several clinical studies in BPD show increased brain areas, reduced neuronal loss, reduced risk of dementia and one study showed improvement in neurocognitive function (verbal memory) associated with increased hippocampal size in lithium- treated groups versus controls, and other medications. The main areas were hippocampus (HC), anterior cingulate and prefrontal cortex (PFC). Functional Studies with N-Acetyl-aspartate (NAA) also support this hypothesis. Conclusions: Despite basic, structural and functional evidence that shows neurotrophic and neuroprotective effect of lithium, longitudinal studies are needed to clarify the clinical relevance of these findings and their correlation with cognitive performance, which seems to be directly related with functional outcome.